RASIONALITAS OBAT ANTI TUBERKULOSIS PADA PASIEN TB PARU RAWAT INAP DI RUMAH SAKIT UMUM KOTA TANGERANG SELATAN - Nurwulan Adi Ismaya; Riris Andriati; Aripin Aripin; Tri Okta Ratnaningtyas; Faizah Tafdhiila (STIKes Kharisma Persada, 2021)
One of disease that continues to be a major global health issue is Tuberculosis. This research aims to evaluate a rational of anti-tuberculosis drugs with patient in pulmonary TB at South Tangerang City General Hospital in 2020. The research design was carried out using a descriptive research method. Descriptive research method is carried out with aapproach retrospective. A total sampling technique was used to collect data from 124 patients. According to the study's findings, the age characteristics of the majority of tuberculosis patients were in late adults 36-45 years as many as 28 patients (22.58 percent), and the majority of gender characteristics were male as many as 83 patients (66.93%), diagnoses and diseases The most co-morbidities of tuberculosis patients were pulmonary TB + Type 2 DM patients with a total of 19 patients (15.32%), the category of treatment for the most tuberculosis patients was in category 1, which was 105 patients (84.67%). Presentation of drug rationale includes 100% correct diagnosis, 100% correct indication, 100% correct drug, 88.70% correct dose, 100% correct route of administration, 98,38% correct time interval, and 100% correct patient. It is possible to conclude that the evaluation of the use of anti-tuberculosis drugs in pulmonary TB patients at South Tangerang City General Hospital's Inpatient Installation is not rational.ABSTRAKSalah satu penyakit menular yang masih menjadi masalah utama kesehatan yaitu Tuberkuloasis. Penelitian ini bertujuan untuk menganalisa kerasionalan obat anti tuberkulosis pada pasien TB paru Rawat Inap di Rumah Sakit Umum Kota Tangerang Selatan Tahun 2020. Penelitian ini adalah penelitian deskripti dengan pendekatan kuantitatif. Data yang digunakan adalah data retrospektif yaitu data tahun 2020 dan pengambilan sampel dilakukan dengan menggunakan teknik total sampling dengan jumlah 124 pasien. Hasil penelitian ini, usia pasien tuberkulosis terbanyak yaitu pada dewasa akhir 36-45 tahun sejumlah 28 pasien (22,58%), pasien terbanyak adalah laki-laki 83 pasien (66,93%), diagnosa dan penyakit penyerta terbanyak pasien tuberkulosis yaitu terdapat pada pasien TB Paru + DM Tipe 2 dengan jumlah 19 pasien (15,32%), kategori pengobatan pada pasien tuberkulosis terbanyak yaitu pada kategori 1 yaitu sebanyak 105 pasien (84,67%). Presentasi kerasionalan obat meliputi tepat diagnosis 100%, tepat indikasi 100%, tepat obat 100%, tepat dosis 88,70%, tepat cara pemberian 100%, tepat interval waktu pemberian 98,38%, dan tepat pasien 100%. Dapat disimpukan bahwa penggunaan obat anti tuberkulosis pada pasien TB paru rawat inap RSU Kota Tangerang Selatan belum rasional.